The management of teething disorder on children - Fajriani (Makassar Dental Journal PDGI Makassar, 2020)
Teething is a normal part of the developmental phase of the teeth that occurs when the baby's first teeth begin to grow, namely deciduous teeth that appear sequentially on the gum surface. Teething usually begins when the baby is between 6-8 months old; the tooth growth occurs when hormones are released in the body causing a number of cells in the gingiva to die and separate so that deciduous teeth can appear. Although teething is a natural process that occurs in the growth of a child's teeth, sometimes it causes pain and discomfort causes parents to experience anxiety. This paper aims to provide an explanation of the theory of teething in handling teething cases.